2013
DOI: 10.1128/genomea.00184-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Chinese Strain of “ Candidatus Liberibacter asiaticus”

Abstract: We report here the complete genome sequence of “Candidatus Liberibacter asiaticus” (strain Guangxi-1). The 1,268,237-bp genome with a 36.5% G+C content comprises 1,141 open reading frames, 44 tRNAs, and 3 complete rRNAs in a circular chromosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 7 publications
0
43
1
2
Order By: Relevance
“…aAccession number AP014595.bAccession number CP001677 [21].cAccession number CP004005 [28].dAccession number NC_014774 [37].eGC contents were calculated using GENETYX ver. 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aAccession number AP014595.bAccession number CP001677 [21].cAccession number CP004005 [28].dAccession number NC_014774 [37].eGC contents were calculated using GENETYX ver. 11.…”
Section: Resultsmentioning
confidence: 99%
“…L. asiaticus’ Chinese gxpsy strain. The accession number is CP004005 [28].dProducts on the same line indicates that the deduced amino acid sequences has a huge similarity to one of ‘ Ca. L. asiaticus’ Floridian psy62 strain on the far left.…”
Section: Resultsmentioning
confidence: 99%
“…Las strain gxpsy (taxid: 1174529, GenBank accession no. CP004005; Lin et al, 2013); Las strain ishi-1 (taxid: 931202, GenBank accession no. NZ_AP014595; Katoh et al, 2014); Lam strain São Paulo (taxid: 1261131, GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…; Lin et al. ). PCR amplification with the primer set showed that all 267 samples yielded amplicons ranging from 1400 bp to 2000 bp.…”
Section: Resultsmentioning
confidence: 98%